High Performance Cross Platform Architecture for Desktop Applications - Maji, Anurag (TIET, 2018)
Amid most recent the quantity of desktop applications has been always developing. Windows MAC OS X and Linux are three vital stages that cover almost all desktops on the planet. Building up an application includes first to pick the stages on which application will run and after that to create particular arrangements i.e. stage particular application for each picked stage utilizing stage related toolboxes. A cross-platform application is an application that keeps running on various stages. A few structures have been proposed to improve the advancement of cross-stage applications and to lessen improvement and upkeep costs. They are called cross-stage application improvement structures. Anyway as far as anyone is concerned the life-cycle and the nature of cross-stages applications fabricated utilizing those systems have a few confinements. In our thesis we introduces a new architecture for desktop applications which will easily allow integrating common components with the platform specific components and will be implemented in an existing application which is implemented for MAC and windows and in which we recreate the architecture for windows version of the existing application of the previous release and created high performance architecture for windows. The application which we implemented is a backend application of the WD Discovery which is a front end portal application provides the user interface of WD Discovery application which is in Node JS and our application is WD Drive Agent which is in windows C++ for Windows and in objective C for MAC application. WD Drive Agent is faceless application. We also explain the integration of direct-attached storage (DAS) applications i.e. WD Drive Agent with Portal Application i.e. WD Discovery. Our main goal is to first study the processes of development and maintenance of applications built using cross-platform application development frameworks, and then to create common code for existing (DAS) applications both for MAC and Windows and improve the performance of the (DAS) applications and integrate it with portal application.
Master of Technology- CSA
Keywords: Cross-Platform Application; DAS; Desktop Application Architecture